Analysis of the interaction and offensive network of the Portuguese national team at the 2016 European Football Championship - Ricardo Alves; Tiago Sousa; Vasco Vaz; Hugo Sarmento; Paul Bradley; Gonçalo Dias (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study was to analyse the offensive actions preceding shots, using a combination of pass sequences and network analysis of the Portuguese national football team in the European Championships. The sample consisted in the observation and analysis of 118 collective offensive actions that ended in a shot based on seven European Championships matches (e.g., 3 x group stage matches, 1 x round of 16, 1 x quarter-finals, 1 x semi-finals and 1 x final). The results indicated that 488 intra-team interactions were performed, and the highest level of interactions occurred between player number 10 (midfielder) and player number 7 (forward), with a total of 11 interactions. More passes were made during the group phase (97.3 ± 50.1 passes), compared with the knockout phase (49 ± 23.6 passes), assuming that the team adapted to their rivals during the last phase of the competition. The InStat© platform was used to access the matches in a video file format and consequently coded through the VideObserver® and Upato® software’s. This study demonstrates important trends in relation to passing sequences and adds key insights into interactional context within and between players during a European Championships. On a practical level with this type of analysis, coaches can characterise the standard actions of a team, as well as identify key players. This may allow coaches to realize what players contribute in the dynamics of their team as well as the opponent.